Ecological model and systems of moral, cultural and legal regulation as risk and protection factors againts substances abuse among students of the University of Nariño - Chaves Cerón, Margarita; Luna Tascón, Edwin Gerardo; Ceballos Mora, Ana Karen; Guerrero Fajardo, Viviana (Universidad y Salud, 2013)
Objective: The purpose of this study was to analyze risk and protection factors against substance abuse among students of the University of Nariño from the perspective of the ecological model and the characteristics of moral, cultural and legal regulation of this phenomenon. Method: The study was conducted from the quantitative paradigm which is framed in analytical studies, specifically a cross-sectional study. Results: The data show that two of the variables that are part of the students’ microsystem behave as risk factors for substance abuse. These are: smoking more than three cigarettes a day and watching parents or stepparents physically attacking themselves. Moreover, moral regulation is the only factor that was identified as the protector one. Conclusion: The results of the study highlight the importance of the variables that are part of the nearest context to the person (including their own habits and rules) as determinants of risk behaviors that compromise the individual and collective welfare and perception of moral regulation as a protective factor.